Students’ engagement in Philippine tertiary PE program: a path for enhancing experience and curriculum development - L. Tagare, Jr., Ruben; A. Vergara, Lordinio; A. Porto, Jerome; Rosita A. Hernani, Maria; Gazali, Novri (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aims to assess student engagement across several dimensions of the PATH-Fit program and explore the interrelationships among these dimensions to inform curriculum development and enhance students’ experience. Using a quantitative research design, precisely a descriptive correlation approach, the study employed a modified research instrument to measure various aspects of student engagement, including Interest and Motivation, Perceived Benefits, Teaching and Learning Environment, Assessment and Feedback, and Overall Satisfaction. A sample of 633 college students from Southern Philippines was selected using simple random sampling to ensure representative and unbiased data. The results reveal that students exhibit moderate engagement in the PATH-Fit program. Analysis shows significant relationships among all engagement variables, indicating that improvements in one area, such as the teaching and learning environment, can positively influence others, like interest and motivation. The interrelationships highlight the interconnectedness of engagement dimensions, suggesting that a holistic approach is necessary for enhancing overall student involvement. In conclusion, while the PATH-Fit program succeeds in capturing students' interest to some extent, there is considerable potential for increasing engagement. By addressing multiple dimensions of engagement simultaneously, the program can better meet students' needs and improve their overall satisfaction and involvement.